2009
DOI: 10.1038/cdd.2009.149
|View full text |Cite
|
Sign up to set email alerts
|

The receptor for advanced glycation end products (RAGE) sustains autophagy and limits apoptosis, promoting pancreatic tumor cell survival

Abstract: Activation of the induced receptor for advanced glycation endproducts (RAGE) leads to initiation of NF-κB and MAP kinase signaling pathways resulting in propagation and perpetuation of inflammation. RAGE knock out animals are less susceptible to acute inflammation and carcinogen induced tumor development. We have reported that most forms of tumor cell death result in release of the RAGE ligand, HMGB1. We now report a novel role for RAGE in the tumor cell response to stress. Targeted knockdown of RAGE in the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
273
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 287 publications
(286 citation statements)
references
References 45 publications
(61 reference statements)
10
273
1
2
Order By: Relevance
“…Moreover, RAGE sustains autophagy and limits apoptosis, promoting pancreatic tumor cell survival in vivo and in vitro. 54,55 In contrast, oxidized HMGB1 increases the cytotoxicity of these agents and induces apoptosis via the mitochondrial pathway. We propose a new function for HMGB1 within the tumor microenvironment: as a regulator of cell death and survival, suggesting that HMGB1 has an important functional role in cross-regulating apoptosis and autophagy.…”
Section: Other Beclin 1-binding Proteins In Autophagymentioning
confidence: 99%
“…Moreover, RAGE sustains autophagy and limits apoptosis, promoting pancreatic tumor cell survival in vivo and in vitro. 54,55 In contrast, oxidized HMGB1 increases the cytotoxicity of these agents and induces apoptosis via the mitochondrial pathway. We propose a new function for HMGB1 within the tumor microenvironment: as a regulator of cell death and survival, suggesting that HMGB1 has an important functional role in cross-regulating apoptosis and autophagy.…”
Section: Other Beclin 1-binding Proteins In Autophagymentioning
confidence: 99%
“…Moreover, HMGB1 promotes stem cell migration and proliferation, and recruitment of acute inflammatory cells including macrophages and neutrophils (Lotze and Tracey, 2005;Tang et al, 2010d). One of the HMGB1 receptors, receptor for advanced glycation end products, has been implicated in tumorigenesis, metastasis, apoptosis and autophagy (Taguchi et al, 2000;Gebhardt et al, 2008;Kang et al, 2010). Thus DAMPs and the associated DAMP receptors within the tumor microenvironment are an attractive target for improving cancer therapy and possibly, for cancer prevention (Figure 1e).…”
mentioning
confidence: 99%
“…10 Moreover, receptor for advanced glycation end products and HMGB1 sustain autophagy and limits apoptosis, promoting pancreatic and colon tumor cell survival. [11][12][13] We have previously demonstrated that endogenous HMGB1 is a negative regulator of apoptosis in leukemia cells. 14,15 Overexpression of HMGB1 by gene transfection rendered leukemia cells resistant to apoptosis; whereas suppression of HMGB1 expression by RNA interference increased the sensitivity of leukemia cells to chemotherapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%